0853 Adiposity In Mexico City Adolescents: The Interplay Of Sleep Duration And Sleep Variability. (27th April 2018) - Jansen, E; Dunietz, G; Chervin, R; Baylin, A; Baek, J; Banker, M; Song, P; Cantoral, A; Tellez Rojo, M; Peterson, K
Abstract: Introduction: Insufficient sleep predicts adolescent obesity prospectively. Sleep variability has also been associated with adiposity among adolescents, although studies are scarce and findings inconsistent. Furthermore, previous studies examined independent associations of sleep duration and sleep variability rather than sleep duration and sleep variability in combination. Methods: In a cohort of 528 Mexico City adolescents aged 9 to 17 years, actigraphy was used to assess sleep. Sleep duration was averaged across the wear time (5–7 days), and categorized into sufficient or insufficient for age (American Academy of Sleep Medicine recommendations). Sleep variability was calculated as the standard deviation of the sleep duration, and split at the median into stable versus variable. Adiposity measures -- body mass index, triceps skinfolds, waist circumference, and percent body fat-- were collected by trained assistants. We conducted linear regression analyses with adiposity measures as the outcome (each in separate models) and combinations of sleep duration and sleep variability as the exposure (insufficient-stable, insufficient-variable, sufficient-stable (reference), and sufficient-variable). Log binomial models were used to estimate prevalence ratios (PR) and 95% confidence interval (CI) for obesity, by joint sleep duration and sleep variability categories. Adjusted models included sex, age, and maternal education. Results: Approximately 40% of the adolescents had insufficient sleep, and 13% were obese. Relative to sufficient-stable sleepers, adolescents with insufficient-stable sleep had higher adiposity across all four measures (e.g. adjusted difference in BMI-for-age z scores was 0.68, 95% CI 0.35, 1.00); and had a greater than twofold higher obesity prevalence (PR=2.54 95% CI 1.36, 4.75). Insufficient-variable sleepers had slightly higher adiposity than sufficient-stable sleepers, although not across all measures. Conclusion: Adolescents with insufficient sleep on a regular basis may be at particular risk of obesity. The fact that insufficient-variable sleepers had only slightly higher adiposity than sufficient-stable sleepers suggests that "catch-up sleep" may play a protective role in adiposity gain. Support (If Any): Dr. Jansen was supported by a T32 grant from the National Institute of Diabetes and Digestive and Kidney Diseases (5T32DK071212-12).